Hemostasis and Thrombosis in Major Liver Resection - Cross, Andrea J.; Connor, Saxon J. (Seminars in Thrombosis and Hemostasis, 2015)
The liver plays an important role in the balance between hemostasis and thrombosis. Hepatic resection, particularly when performed in the presence of underlying parenchymal liver disease, can cause perturbation of this balance. This review summarizes the changes that occur in normal hemostasis and thrombosis before, during, and after nontransplant hepatic resection and, wherever possible, provides strategies for the perioperative management of bleeding and thrombosis.
Keywords: liver resection; hemostasis; thrombosis